Time-course observation of the reconstruction of stem cell niche in the intact root. Issue 4 (3rd February 2021) - Xu, Meizhi; Gu, Xu; Yu, Qiaozhi; Liu, Yuting; Bian, Xinxin; Wang, Renyin; Yang, Meina; Wu, Shuang
Abstract: The stem cell niche (SCN) is critical in maintaining continuous postembryonic growth of the plant root. During their growth in soil, plant roots are often challenged by various biotic or abiotic stresses, resulting in damage to the SCN. This can be repaired by the reconstruction of a functional SCN. Previous studies examining the SCN's reconstruction often introduce physical damage including laser ablation or surgical excision. In this study, we performed a time-course observation of the SCN reconstruction in pWOX5:icals3m roots, an inducible system that causes non-invasive SCN differentiation upon induction of estradiol on Arabidopsis ( Arabidopsis thaliana ) root. We found a stage-dependent reconstruction of SCN in pWOX5:icals3m roots, with division-driven anatomic reorganization in the early stage of the SCN recovery, and cell fate specification of new SCN in later stages. During the recovery of the SCN, the local accumulation of auxin was coincident with the cell division pattern, exhibiting a spatial shift in the root tip. In the early stage, division mostly occurred in the neighboring stele to the SCN position, while division in endodermal layers seemed to contribute more in the later stages, when the SCN was specified. The precise re-positioning of SCN seemed to be determined by mutual antagonism between auxin and cytokinin, a conserved mechanism that also regulates damage-induced root regeneration. Our results thus provide time-course information about the reconstruction of SCN in intact Arabidopsis roots, which highlights the stage-dependent re-patterning in response to differentiated quiescent center. Abstract : Time course live imaging technique revealed stage-dependent reconstruction patterns of stem cells in the intact Arabidopsis roots in response to differentiated quiescent center.